Design Level Shifted Multicarrier Techniques for Cascaded H-Bridge Sub-Multilevel Inverter - Javed Jamshed Korai; Mukhtiar Ahmed Mahar; Abdul Sattar Larik; Fazal Ur Rehman Soomro; Imran Ali; Muhammad Samiullah Awan (Journal of ICT, Design, Engineering and Technological Science, 2020)
The key aim of this paper is to implement and analyze level-shifted multicarrier techniques in Cascaded H Bridge (CHB) - Sub multi-level inverter to produce multiple level output voltage. The multi-level inverter is to synthesize a near sinusoidal voltage from several levels of dc voltages. The asymmetrical DC voltage sources are used for CHB Sub-Multilevel inverter, and the 15-level output voltage is obtained. The asymmetrical DC voltage Sources 12V, 24V, and 48V are used to get the 15 Level output voltage. The multicarrier Pulse Width Modulation (PWM) is used to get the desired voltage at the output. The Level Shifted Phase Disposition (LSPD) and Level Shifted Phase Opposition Disposition (LS-POD) multicarrier PWM techniques are used to reduce the Total Harmonic Distortion (THD) in the output voltage. The circuit is developed and analyzed in MATLAB software. The THD, measured by using the FFT tool of MATLAB software From the simulated results, the level-shifted phase opposition disposition multicarrier PWM has better performance than level-shifted phase disposition multicarrier PWM technique because it contains fewer harmonics so to improve the system reliability and quality. The performance analysis and mitigation of harmonics can enhance the power quality of the supply voltage delivered to the customers. However, power quality occurs several problems such as voltage sag, swell, under-voltage, overvoltage, transients, etc.